SME's processed frozen food packaging perceived hedonic and utilitarian value influence customers buying decision/ Aidza Ashikin Alias and Ali Mohamad Noor - Alias, Aidza Ashikin; Mohamad Noor, Ali (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2022)
This study explores the influence of hedonic and utilitarian values of food packaging design that influences customers' buying decision. It focused on processed frozen food produced by small and medium enterprise (SME) in Malaysia. There are substantial numbers of SME'S that were registered in Malaysia and one of the categories are including food processing sector. However, these enterprises lack of knowledge in marketing strategy particularly in food packaging design to compete in highly competitive market. Six (6) elements of food packaging design which is images, colours, sizes, materials, shapes, and labels are investigated. These elements have an obvious significant relation toward the hedonic and utilitarian values on packaging. The study approaches causal research design on finding the effect of the independent variable (food packaging design perceived hedonic and utilitarian value) towards the dependent variable (customers' buying decision of a processed food product). The data were collected by online survey questionnaire among customers that aware, consumed and purchased SME processed frozen food in Selangor, Malaysia. The questionnaire was distributed on an online platform and to respondents that are residing in Selangor, Malaysia. A total of 263 responses were received, only 243 respondents answered "yes" on familiarity, consuming, or purchasing SME processed frozen food products. As for the finding of the study, it is found that the right elements of food packaging design have relationship in customers decision. The hedonic and utilitarian attributes have a considerable contributing proportion in influencing customers purchase decision. Overall, this study provides an exciting opportunity to advance the knowledge of food packaging design that perceive hedonic and utilitarian value for customers to purchase SMEs processed frozen food.